2019
DOI: 10.5713/ajas.18.0780
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ultrasound and adenosine 5’-monophosphate marination on tenderness and structure of myofibrillar proteins of beef

Abstract: Objective The aim was to investigate the influence of ultrasound and adenosine 5′-monophosphate (AMP) marination (UAMP) on tenderness and structure of myofibrillar proteins of beef. Methods Five groups, the untreated meat (Control), deionized water marination (DW), ultrasound followed by DW (UDW), AMP marination (AMP), and ultrasound followed by AMP (UAMP) were studied. Myofibrillar fragmentation, cooking loss, shear force, thermograms, histological observation of meats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…The ionic strength of AMP leads to the alteration of the meat surface environment, thus affecting its stronger capacity to retain water ( Shao et al., 2016 ) and the creation of more space within myofibrils to avoid intracellular release of water ( Honikel et al., 1986 ). These significant findings corresponded to previous studies on the semimembranosus muscle of cattle ( Zou et al., 2019 ) and duck breast meat ( Wang et al., 2015 ).…”
Section: Resultssupporting
confidence: 91%
“…The ionic strength of AMP leads to the alteration of the meat surface environment, thus affecting its stronger capacity to retain water ( Shao et al., 2016 ) and the creation of more space within myofibrils to avoid intracellular release of water ( Honikel et al., 1986 ). These significant findings corresponded to previous studies on the semimembranosus muscle of cattle ( Zou et al., 2019 ) and duck breast meat ( Wang et al., 2015 ).…”
Section: Resultssupporting
confidence: 91%
“…1b]. This effect was similar to that of ultrasound-assisted sodium bicarbonate curing on tender chicken breast, which was reported by Xiong et al (2020 andZou et al (2019b). Gonzalez-Gonzalez reported that ultrasonic treatment tenderised and accelerated beef maturation (Gonzalez-Gonzalez et al, 2020).…”
Section: Effect Of Curing On the Shearing Force Of Chicken Breast Meatsupporting
confidence: 74%
“…(2020 and Zou et al . (2019b). Gonzalez‐Gonzalez reported that ultrasonic treatment tenderised and accelerated beef maturation (Gonzalez‐Gonzalez et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sriket et al [33] indicated that MHC was more likely to cause protein degradation than other proteins. Thus, it is most likely that the turbulent flow and shear force associated with ultrasonic cavitation dissociated the complex structure of MPs [2] , [34] and increased their accessibility. This makes MHC in MPs vulnerable to fragmenting into small particles, in effect leading to protein degradation in the present study.…”
Section: Resultsmentioning
confidence: 99%